It's very basic but I'm having trouble to find a way to prove this inequality


when $x>1$

($\log(x)$ is the natural logarithm)

I can think about the two graphs but I can't find an other way to prove it, and, besides that, I don't understand why should it not hold if $x<1$

Can anyone help me?

Thanks in avice


12 Answers 12


You may just differentiate $$ f(x):=\log x-x, \quad x\geq1, $$ giving $$ f'(x)=\frac1x-1=\frac{1-x}x<0 \quad \text{for}\quad x>1 $$ since $$ f(1)=-1<0 $$ and $f$ is strictly decreasing, then $$ f(x)<0, \quad x>1, $$ that is $$ \log x -x <0, \quad x>1. $$


I thought it might be instructive to present a proof that relies on standard tools only. We begin with the limit definition of the exponential function

$$e^x=\lim_{n\to \infty}\left(1+\frac xn\right)^n$$

It is easy to show that the sequence $e_n(x)=\left(1+\frac xn\right)^n$ increases monotonically for $x>-1$. To show this we simply analyze the ratio

$$\begin{align} \frac{e_{n+1}(x)}{e_n(x)}&=\frac{\left(1+\frac x{n+1}\right)^{n+1}}{\left(1+\frac xn\right)^n}\\\\ &=\left(1+\frac{-x}{(n+x)(n+1)}\right)^{n+1}\left(1+\frac xn\right) \tag 1\\\\ &\ge \left(1+\frac{-x}{n+x}\right)\left(1+\frac xn\right)\tag 2\\\\ &=1 \end{align}$$

where in going from $(1)$ to $(2)$ we used Bernoulli's Inequality. Note that $(2)$ is valid whenever $n>-x$ or $x>-n$.

Since $e_n(x)$ monotonically increases and is bounded above by $e^x$, then

$$e^x\ge \left(1+\frac xn\right)^n \tag 3$$

for all $n\ge 1$. And therefore, for $x>-1$ we have

$$e^x\ge 1+x \tag 4$$

Since $e^x>0$ for all $x$, then $(4)$ is true for $x\le -1$ also. Therefore, $e^x\ge 1+x$ for all $x$.


From $(4)$ we note that $e^{-x}\ge 1-x$. If $x<1$, then since $e^x\,e^{-x}=1$, $e^x\le \frac{1}{1-x}$. Thus, for $x<1$ we can write

$$1+x\le e^x\le \frac{1}{1-x}$$

Taking the logarithm of both sides of $(4)$ produces the coveted inequality

$$\log(1+x)\le x \tag 5$$

Interestingly, setting $x=-z/(z+1)$ into $(4)$ reveals

$$\log(1+z)\ge \frac{z}{z+1}$$

for $z>-1$. Putting it all together we have for $x>0$

$$\frac{x-1}{x}\le \log x\le x-1<x$$


I am assuming you know the derivative of $\log$.

Let $f(x)=\log x -x$. Then $$f'(x) = \frac 1x -1<0\ \ \forall x>1.$$ Moreover, $f(1) = -1<0$. So you have a function that starts negative at $x=1$, and decreases afterwards since its derivative is always negative. This means that $$f(x) = \log(x) - x <0\ \ \forall x>1,$$ which is what you wanted to show.


If you defined the logarithm as $$\log(x)=\int_{1}^{x}{\frac{1}{x}dx},$$ $$\frac{1}{x} \le 1 \; \text{ for }x\ge 1.$$ Hence, $$ \log(x)=\int_{1}^{x}{\frac{1}{x}\,dx} \le \int_{1}^{x}\!{1}\,dx =x-1 \le x.$$ If $0< x\le 1\;$ then you simply get $$\log(x)=\int_{1}^{x}{\frac{1}{x}\,dx}=- \int_{x}^{1}{\frac{1}{x}\,dx}\le 0 < x.$$


You even have $\;\log x \le x-1$, because $\log$ is a concave function, and the line with equation $y=x-1$ is the tangent to the graph of $\log$ at $(1,0)$. Hence: $$\log x \le x-1 <x. $$


Taylor series give $$e^x = 1 + x + \frac{x^2}{2} + \frac{x^3}{6} + \cdots$$

Hence $e^x > 1+x > x$ for $x\geq0$, so $\log(e^x) > \log(x)$ since $\log$ is increasing. Hence $x > \log(x)$ for $x\geq0$.

  • $\begingroup$ Damn, beat me to it! I find this to be the simplest proof. $\endgroup$ – Laplacinator Jul 31 '17 at 12:46

Define $f(x) = \log x - x$. Now $f'(x) = \frac{1}{x}-1$ which is negative if $x > 1$. Thus $f$ is strictly decreasing on the interval $(1, \infty)$.

Now since $f(1) = \log 1 - 1 = 0-1 = -1$, we must have $f(x) < -1$ on $(1, \infty)$. Thus $\log x - x < -1 < 0$ on $(1, \infty)$. This implies $\log x < x$ when $x > 1$.


When $x=1$, $\log x=0<1=x$. Further, for $x>1$ we have $\frac{d}{dx}\log x=\frac{1}{x}<1=\frac{d}{dx}x$.

This shows that $x$ is larger than $\log x$ at $x=1$ and that $x$ grows faster than $\log x$ for $x>1$. Hence $x>\log x$ for $x\ge 1$.


$\log_{10}x<x$ implies $x<10^x$ We can directly see it by observation and is true for all $x$. Or directly go for derivatives!

  • 1
    $\begingroup$ The OP defined log as the natural log $\endgroup$ – GaussTheBauss Dec 26 '15 at 12:34
  • $\begingroup$ May be it of any type 10 raised to x can nver be less than x thats i gave it as soln $\endgroup$ – Archis Welankar Dec 26 '15 at 12:37

different ways of doing this exercise certainly depend on what you wish to assume. suppose we take $\log x$ to be a continuous non-constant map $f:\mathbb{R}^+ \to \mathbb{R}$ satisfying $$ f(xy) = f(x)+f(y) \tag{1} $$ this immediately gives $f(1)=0, f(x)+f(\frac1{x})=0$ so $f$ is a non-trivial abelian group homomorphism with $\exists c\dot f(c) \ne 0$

(1) implies that for any integers $m,n \ne 0$ we have $$ \log \sqrt{[n]c^m}=\log c^{\frac{m}{n}}= \frac{m}{n} \log c \tag{2} $$ since for $\mathbb{R}^+\ni x \ne 1$ the set $\{c^{\frac{m}{n}}\}_{m,n \in \mathbb{Z}\setminus \{0\}}$ is dense in $\mathbb{R}^+$ we have, by continuity, $$ f(c^r)=r\log c $$ for any $r \in \mathbb{R}^+$

(2), together with the density of $\text{Im}(f)$ in $\mathbb{R}^+$ (1) implies that $f$ is order-preserving or order-inverting depending on the sign of $\log c$ and whether $c \gt 1$. thus to rule out the order anti-isomorphisms we require one further assumption, that $f((1,\infty)) \subseteq (0,\infty)$

suppose $f$ had a fixed point $\zeta \gt 1$. i.e a point for which as real numbers $$ f(\zeta) = \zeta $$ we will show this leads to a contradiction.

since $f(1)=0$ and $f$ is strictly monotonic and continuous the equation $f(x)=1$ has a unique solution, let us say $x=e \gt 1$.

since $\text{Im}(f)\subset \text{Domain}(f)$ we may define a sequence of functions $f_n$ with $\text{Domain}(f_{n+1})=F_{n+1} = \text{Im}(f_n)$ and $f_{n+1}=f_{|F_{n+1}}$ renaming $f$ as $f_0$ we have a sequence $F_n$ with $$ F_{n}=(e^n,\infty) \\ \bigcap F_n = \emptyset $$ but $\forall n \zeta \in \text{Image} (f_n)$, contradiction

since $f$ has no fixed point and $f(1) \lt 1$ we have our result

  • 1
    $\begingroup$ How does this answer the question? $\endgroup$ – Pedro Tamaroff Dec 27 '15 at 6:51
  • $\begingroup$ @Pedro my thought was that if $x \gt \log x$ when $x=1$ and there is no $x$ for which $\log x = x$ then since $x$ and $\log x$ are continuous the inequality must hold for $x \ge 1$ $\endgroup$ – David Holden Dec 27 '15 at 9:45

Note that the second derivative of $\ln(x)$ is $-\frac{1}{x^2}$, which is always negative. This means that any tangent line to the graph $y=\ln(x)$ will be greater than or equal to $\ln(x)$, equality only being achieved at the tangent point. We can then conclude that the tangent line $x-1$ is greater than or equal to $ln(x)$. Since $x>x-1$, $x>\ln(x)$ for any value of $x$.


If you're familiar with the Taylor Theorem, this is a short proof of the inequality:

Define $f(x)=\log(x)$ for $x>0$. I'm going to assume that the natural logarithm is the (only) function which verifies that $f(1)=0$ and $f'(x)=\dfrac{1}{x}$ (this is one of the many definitions we can give, others would be to say it's the inverse function of the exponential function, $e^{x}$, or saying it is the integral $\int_{1}^{x}\dfrac{1}{t}dt$, but that's not the problem now).

The second derivative of $f$ is $f''(x)=-\dfrac{1}{x^{2}}$, continuous in $(0,\infty)$.

Let's take a point $x>1$, since $f$ is a $\mathcal{C}^{2}$ function (its first and second derivatives exist and are continuous), the Taylor Theorem guarantees that there exists $c\in (1,x)$ which satisfies




But since $c^{2}>0$ and $(x-1)^{2}>0$, we know that

$\log(x)<x-1<x$, which is what we wanted to prove.

Even though the question was made only considering $x>1$, the result is also true when $x\leq 1$. The case $x<1$ would be solved in the same manner, whereas doing it while $x=1$ is just a matter of checking directly.

  • $\begingroup$ Typesetting hint: use a backslash (\log) to get $\log$ instead of $log$ (which looks like a product of $l,o,g$). The same goes for $\sin, \ker$, etc. $\endgroup$ – Théophile Jul 10 '18 at 19:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.